Mengapa Asesmen Psikologi Penting dalam Bimbingan dan Konseling (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Psychological assessment plays an important role in guidance and counseling, especially in understanding the psychological condition of the client and increasing the effectiveness of the intervention provided. This study aims to explore the function of psychological assessment in guidance and counseling, analyze its benefits in improving the quality of services, and identify the challenges faced in its implementation. The research method used is a literature study with a descriptive and exploratory approach, which aims to analyze data from various academic sources related to psychological assessment. The results of the study indicate that systematic assessment can help counselors understand clients, find appropriate intervention strategies, and launch client development after receiving intervention. However, challenges in implementing assessments, such as limited valid measuring instruments and client resistance, are still obstacles to its effectiveness. The implications of this study indicate that improving the quality of assessment through counselor training, developing more adaptive assessment methods, and educating clients can improve the effectiveness of guidance and counseling as well as individual psychological well-being.